Analisis Faktor yang Berpengaruh Terhadap Keluhan Pruritus pada Lansia di Panti Pangesti Lawang - Oda Debora (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2019)
Background: Older people experienced significant changes in integument anatomy and physiology. Older people often reported chief complaints of itching or pruritus for dermatology problem when they came to the healthcare facility. This complaint was also expressed by the older people who were hospitalized and at nursing home. Eventhough it was only itch, prolonged condition can lead to quality of life degradation. Purpose: This research aimed was to analyze the factors which most influenced the complaint of pruritus in older people who were at nursing home. Factors analyzed were skin water content, skin oil content, and the older people functional ability. Methods: This research was a non-experimental study with a cross-sectional study design. The study was conducted in a nursing home with 30 elderly respondents taken using purposive sampling technique. Itching complaints were assessed using a questionnaire, while water and oil content data were obtained through direct measurements documented in an observational sheet. Data on elderly functional abilities was measured using the Barthel Index. The data obtained was processed using logistic regression to determine the factors which influenced pruritus complaints. Result: In sequence, the variable water content in the skin, oil content in the skin, and the functional ability of the body have a p value of 0.004 (coefficient of influence of -0.129), 0.009 (coefficient of influence of -0.383) and 0.007 (coefficient of influence of -0.721). Conclusion: Water and oil content, also body functional ability sequentially affect the complaints of pruritus revealed by the elderly. Nursing procedures which can be done by nurses to overcome these problems was to pay attention to skin moisture and optimize mobilization so that air circulation in the pores was smoother and skin is not too moist.